Degradation of Natural Rubber as Asphalt Mixes Modifier using UV-Ozone Light - Ritonga, Irene I. C.; Tamrin, Tamrin; Marpongahtun, Marpongahtun (Jurnal Akademika Kimia, 2023)
The elastic properties of natural rubber are indispensable in improving the physical properties of asphalt mixtures. However, the long natural rubber molecule chains make it difficult to modify with other polymeric materials, so it needs to be degraded. In this study, the authors succeeded in degrading natural rubber using a combination of UV light and ozone with the addition of an H2O2 initiator; from the FTIR data, it appears that there are peaks indicating vibrations of the C=O and –OH groups indicating that natural rubber chain termination has occurred. The addition of natural rubber to asphalt was carried out with several variations, namely 8; 10; 12; 14; 16 % (to asphalt content), from the results of the softening point and ductility test of the asphalt mixture explained that the addition of 12 % natural rubber was the most optimum mixture. This result explains that efforts to degrade natural rubber using the UV - ozone combination method can increase the optimum insertion of natural rubber into asphalt mixtures by up to 100 % from previous studies.